Zdroje EU a projekty partnerství veřejného a soukromého sektoru - Sabolová, Veronika (Univerzita Pardubice, 2007)
The article considers questions of combining European money and PPP and causes of limiting using of this combination to finance Public Private Partnership projects. It analyses generally characteristic of PPP projects, next it mentions Green paper of PPP and basic models of combination of PPP and EU funds as well. It examines in detail limiting combining PPP principles and EU funds and its causes.
Keywords: EU funds; financing projects; Green Paper; public private partnerships